The Effectiveness of ICARE Learning Model in Improving Students’ Critical Thinking Skills and Collaboration Skills - Mawarni Saputri; Elisa Elisa; Siska Nurlianti (Jurnal Penelitian Pendidikan IPA, 2022)
The aim of this study was to know the effectiveness of the ICARE learning model in improving students' critical thinking skills and collaboration skills. The type of research conducted in this research was classroom action research. In this study, there were three stages of data collection namely planning, implementation and data analysis which were analyzed using descriptive statistics. The research instrument used was a critical thinking skill test in essay form, an observation sheet for teacher and student activities in learning, a teacher ability observation sheet, a student response sheet and an observation sheet for students’ collaboration skills. The result showed that ICARE learning model was effective in improving students' critical thinking skills and collaboration skills. The result of students' responses to the ICARE learning model were also very positive. This positive response showed that students were very enthusiastic about the learning presented and make it easier for students to understand the material.